1999
DOI: 10.1161/01.atv.19.6.1393
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle-Specific SM22 Protein Is Expressed in the Adventitial Cells of Balloon-Injured Rabbit Carotid Artery

Abstract: Abstract-During the "response-to-injury" process after a mechanical insult to the porcine coronary arteries, the adventitial cells acquire the structural characteristics of myofibroblasts before being incorporated into smooth muscle (SM) layer.We assessed whether the SM-specific SM22 protein can be used as a tracer of adventitial cell-myofibroblast differentiation in the mild balloon injury of rabbit carotid artery. To achieve this goal, we used 2 monoclonal anti-SM22 antibodies (E-11 and 1-B8) and a molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 69 publications
10
67
0
Order By: Relevance
“…It is possible that fibroblasts present within the connective tissue in vivo not only maintain ECM and connective tissue homeostasis, but also serve as tissue-resident progenitors of skin-associated lineages. Fibroblasts appear to serve as vascular cell progenitors in the injured rabbit carotid artery (Faggin et al, 1999). Large blood vessels, such as the carotid artery, are composed of three distinct layers of tissue, the intima, media, and adventitia.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that fibroblasts present within the connective tissue in vivo not only maintain ECM and connective tissue homeostasis, but also serve as tissue-resident progenitors of skin-associated lineages. Fibroblasts appear to serve as vascular cell progenitors in the injured rabbit carotid artery (Faggin et al, 1999). Large blood vessels, such as the carotid artery, are composed of three distinct layers of tissue, the intima, media, and adventitia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that adventitial passive fibroblasts can become active myofibroblasts under conditions of adventitial inflammation. 10,11 On the other hand, SMCs were the predominant proliferating cell type in the intima. IL-1 itself is mitogen for SMCs, 1 and furthermore, a recent study showed that vascular intima formation after mechanical injury was found to consist mainly of inflammation-associated cells that originated from the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…They are in agreement with current views concerning the pathogenesis of stent-induced lesions, 8 whereas the pathogenesis of PTCA-induced lesions has up to now remained controversial. 6,7,[15][16][17] …”
Section: Discussionmentioning
confidence: 99%
“…16 When fibroblasts transduced with retroviral particles encoding ␤-galactosidase were implanted in the adventitia of the rat carotid artery, some of these cells could be found in neointima formation after balloon injury. 17 The relative proportions of SMCs and fibroblasts participating in neointima formation in that model remain to be established.…”
Section: Smc Marker Expression In Tissues Of Porcine Coronary Arteriamentioning
confidence: 99%